Life expectancy and mortality of people with and without diabetes in Aotearoa | New Zealand: A national cohort study - Francois Verster; Nicholas Bowden; Philip J. Schluter; Lynne Chepulis; Ryan G. Paul (PLoS ONE, 2026)
Background Diabetes mellitus (DM) is a significant driver of excess morbidity and premature mortality, though few contemporary or locally-derived data quantify this impact on New Zealanders, particularly Māori and Pacific Peoples. This prospective, national population study examines the life expectancy (LE) for New Zealanders with and without DM, and characterises mortality rates. Methods Data from 01/01/2015 to 31/12/2019 housed in the Integrated Data Infrastructure, including the Virtual Diabetes Registry and Health New Zealand Mortality Collection, were linked. Estimated remaining LE years were calculated using abridged period life tables using the Chiang method for those with type 1 diabetes (T1D), type 2 diabetes (T2D), and without DM. Sub-group analysis by ethnicity was completed. Five-year cause-specific mortality rates per 100,000 people were compared by DM group. Findings T1D and T2D prevalence was 0.4% and 5.5% in the overall sample ( n = 4,505,478). Considerable ethnic differences in LE were evident, for example a 13-, 17.1-, and 24.5-year loss in remaining LE years was seen in men aged 0–19 years with T1D in the overall, Māori, and Pacific Peoples groups respectively compared to those without DM. An age-dependent reduction in remaining life expectancy years was also evident; for example an 8.6 (8.5–8.7) year reduction seen in females with DM aged 0–4, and 4.0 (4.0–4.1) year reduction for women with DM aged 65–69. Those with DM had higher cause-specific death rates. Interpretation DM is associated with age-dependent reductions in LE across the entire lifespan, with disproportionately higher LE loss seen in Māori and Pacific Peoples.